Challenges of new venture growth in service industry: case study of company secretary in Kelantan, Malaysia. - Siti Som Husin (2018)
The main objective of this research is to explore the challenges that can hinder the growth of the new venture in service industries. The decline of new venture growth could contribute to the deterioration of economic growth. Previous studies on challenges in new venture growth only identified certain issues such as financial, management skills, human resources, technology, customer satisfaction in isolation but not from the holistic perspective. Hence, the context of this study focuses on service industry. This study explores the challenges of new venture growth from entrepreneur, oganisation and environment domains within the service industry in order to understand the phenomenon. To achieve the objectives, this study employs qualitative research methods using an inductive approach, case study strategy and thematic data analysis technique. Four cases of companies secretary were involved in this study. The main data source was the interview transcripts. The interview transcripts has been manually analyzed by using thematic data analysis. This study finally comes out with triadic model that reveals all the challenges in new venture growth in service industry. Future research should focus more on qualitative study but in different context of service industry because each context has different growth challenges and unique characteristic.